Patterns of suicidal ideation and behavior in Northern Ireland and associations with conflict related trauma. - Siobhan O'Neill; Finola Ferry; Sam Murphy; Colette Corry; David Bolton; Barney Devine; Edel Ennis; Brendan Bunting (PLoS ONE)
In this study, data from the World Mental Health Survey's Northern Ireland (NI) Study of Health and Stress (NISHS) was used to assess the associations between conflict- and non-conflict-related traumatic events and suicidal behaviour, controlling for age and gender and the effects of mental disorders in NI. DSM mental disorders and suicidal ideation, plans and attempts were assessed using the Composite International Diagnostic Interview (CIDI) in a multi-stage, clustered area probability household sample (N = 4,340, response rate 68.4%). The traumatic event categories were based on event types listed in the PTSD section of the CIDI. Suicidal ideation and attempts were more common in women than men, however, rates of suicide plans were similar for both genders. People with mood, anxiety and substance disorders were significantly more likely than those without to endorse suicidal ideation, plan or attempt. The highest odds ratios for all suicidal behaviors were for people with any mental disorder. However, the odds of seriously considering suicide were significantly higher for people with conflict and non-conflict-related traumatic events compared with people who had not experienced a traumatic event. The odds of having a suicide plan remain significantly higher for people with conflict-related traumatic events compared to those with only non-conflict-related events and no traumatic events. Finally, the odds of suicide attempt were significantly higher for people who have only non-conflict-related traumatic events compared with the other two categories. The results suggest that traumatic events associated with the NI conflict may be associated with suicidal ideation and plans, and this effect appears to be in addition to that explained by the presence of mental disorders. The reduced rates of suicide attempts among people who have had a conflict-related traumatic event may reflect a higher rate of single, fatal suicide attempts in this population.